A network analysis approach in multidimensional poverty. Issue 1 (23rd March 2021) - García‐Vélez, Diego; Nuñez Velázquez, José J.
Abstract: This paper applies a network analysis approach to weight the dimensions of multidimensional poverty. Weights are allocated according to the interaction of the deprivations to eliminate arbitrary value judgments used in equitable weighting. The approach is applied to a developing country. The results indicate that some dimensions are more relevant than others and measures of poverty show significant differences when changing the weighting approach. 摘要: 本文应用一项网络分析方法，对多维度贫困的各维度赋予权重。根据贫困的相互影响分配权重，以消除在等权（equitable weighting）中使用的任意价值判断。该网络分析方法应用于一个发展中国家。结果表明，一些维度比其他维度更为相关，并且贫困措施显示，当改变加权方法时会出现显著差异。 Resumen: Se propone utilizar el Análisis de Redes Sociales como enfoque para ponderar dimensiones en la pobreza multidimensional. Los pesos se asignan en función de la interacción de las privaciones para eliminar los juicios de valor arbitrarios utilizados en la ponderación equitativa. El enfoque se aplica para un país en vías de desarrollo. Los resultados evidencian que existen dimensiones más relevantes y la pobreza muestra diferencias significativas al cambiar el enfoque de ponderación.